2005
DOI: 10.1038/sj.cgt.7700808
|View full text |Cite
|
Sign up to set email alerts
|

PCI-enhanced adenoviral transduction employs the known uptake mechanism of adenoviral particles

Abstract: The development of methods for efficient and specific delivery of therapeutic genes into target tissues is an important issue for further development of in vivo gene therapy. In the present study, the physical targeting technique, photochemical internalization (PCI), has been used together with adenovirus. The combination of PCI and adenoviral transduction has previously been shown to be favorable compared to adenovirus used alone, and the aim of this study was to verify the role of the adenoviral receptors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The selectivity of the treatment is further enhanced by the tumor preferential localization of the photosensitizers [36], and could additionally be improved by combining PCI with transcriptional and transductional targeted adenovirus. PCI has already been combined successfully with RGD- [21] and EGFR-targeted [37] adenoviruses.…”
Section: Discussionmentioning
confidence: 98%
“…The selectivity of the treatment is further enhanced by the tumor preferential localization of the photosensitizers [36], and could additionally be improved by combining PCI with transcriptional and transductional targeted adenovirus. PCI has already been combined successfully with RGD- [21] and EGFR-targeted [37] adenoviruses.…”
Section: Discussionmentioning
confidence: 98%
“…Selbo et al demonstrated that the use of PCI enhanced the potency of the plant toxin gelonin in inhibiting cellular protein synthesis by a factor of 300 (21). In addition, the low-molecular weight drug bleomycin (22), antigenic peptides (23), immunotoxins (24,25), peptide nucleic acids (26) and even colloidal carriers for gene delivery (27)(28)(29) have been successfully delivered into the cytosol via PCI. These agents generally are not able to reach their intracellular target site efficiently, due to lack of capability to pass cellular membranes and/or the occurrence of degradation within endocytic vesicles.…”
Section: Efficacy Studiesmentioning
confidence: 99%
“…PCI has been shown to increase the cytosolic delivery and subsequent therapeutic effect in vitro of many macromolecules such as proteins (Selbo et al 2000a, Dietze et al 2003, immunotoxins (Selbo et al 2000b, Selbo et al 2001a and DNA delivered by cationic polymers , Prasmickaite et al 2001, adenovirus , Engesaeter et al 2005, Engesaeter et al 2006a, Engesaeter et al 2006b) and adenoassociated virus . PCI in vitro has also been reported as an intracellular delivery system for peptides (Berg et al 1996, Berg et al 1999, PNAs (Shiraishi & Nielsen 2006, siRNA (Oliveira et al 2007) and some chemotherapeutics, such as bleomycin , doxorubicin , Lai et al 2007) and mitoxantrone (Adigbli et al 2007).…”
Section: Pci Of Different Classes Of Moleculesmentioning
confidence: 99%